Risk factors for hypocalcemia after total thyroidectomy: a narrative review - Bohan Cao; Guangzhe Wu (PeerJ)
Hypocalcemia is a frequent complication after total thyroidectomy and seriously affects patients’ postoperative quality of life and long-term prognosis. This article reviews the relationship between postoperative hypocalcemia and its suspected risk factors, including age, sex, serum magnesium, vitamin D, high-risk pathological subtype, parathyroid injury, and parathyroid hormone levels, and assesses the ability of preoperative and postoperative parathyroid hormone levels and changes therein at various time points to predict postoperative hypocalcemia. It also discusses the protection of the parathyroid glands in situ by tracer techniques during total thyroidectomy. The various studies that have concluded that parathyroid injury is the most important indicator of postoperative hypocalcemia among these risk factors are reviewed. It is important for general surgeons to know how to avoid intraoperative parathyroid injury, which will contribute to the prevention of hypocalcemia.